(untitled) (Heritage, 2023)
The necessity to study the statutes of coastal towns under Serbian rule in the Middle Ages stems from the fact that those statutes are actually written laws of those communities. We learn from them that the questions were regulated through customary law. The Skadar Statute, here the subject of our study, originate from the period of the King Stefan Dusan rule, more precisely, before he was crowned king in 1346. The paper is, as much the source allows it ,a comprehensive study of the status of male offspring as given in the Skadar Statute. We have shown how it regulated marriage for minor sons and those of age, the questions of their wives’ dowry, rules of intestacy, disinheritance of sons, issues of both sons’ and parents’ debts, wills made by father, mother and sons, as well as the rules of intestacy when there was no will. The legal issue of the male offspring in the Skadars Statute that has been studied and systematised in this way enables a comparison with the legal status of male offspring in other Serbian coastal towns, primarily of Kotor and Budva.